Evaluation of fine needle aspiration cytology of thyroid lesions based on Bethesda system of reporting cytopathology - Dr. Rajesh H. Chandan; Dr.Arathi S.; Dr. Parvati Jigalur; S. Giriyan, Sujata (Tropical Journal of Pathology and Microbiology, 2019)
Introduction:FNAC is the first line diagnostic test for evaluation of thyroid lesions. Identification of cytological features is key element in diagnosing thyroid lesions, which will reduce the number of unnecessary surgeries of thyroid nodules. Bethesda system of reporting helps the clinicians to take appropriate therapeutic intervention. Aim: To study the cytomorphological features of various thyroid lesions and to categorize as per Bethesda system proposed by NCI Bethesda USA in 2007. Materials and Methods: This is a prospective study of cases of thyroid lesions received in cytology section of Department of Pathology, KIMS Hubballi, during Jan 2017 to Dec 2017. FNAC was performed and reported according to Bethesda system. Results: FNAC was performed on 370 cases of thyroid lesions.Maximum number of cases were in the age group of 21 -30 years.Male to female ratio was 1: 9.27. Maximum number of cases presented in less than 6 month duration. Most of the cases presented with swelling in the neck. Out of the total370cases, 351were benign lesion, 6 cases were malignant, 8 were unsatisfactory, 3 were follicular neoplasm/suspicious of follicular neoplasm, 1 was suspicious for malignancy and 1 was follicular lesions of undetermined significance. Out of 351 benign lesions, commonest was colloid/ nodular goiter, followed by lymphocytic/Hashimotos thyroiditis. Conclusion: FNAC is the most simple, rapid and safe diagnostic test for evaluation of thyroid lesions with high degree of accuracy.Bethesda system of reporting thyroid cytopathology is very useful as it is systematic and standardized and hence provides better communication between clinicians and cytopathologist for appropriate therapeutic intervention.